Leadership style and police attitude among police officers in Digos City - Lorejun G. Ando; Ando, Lorejun G.; Mier, Eduardo A.; Perez, Mark Andie I. (Digos City: UMDC, 2019)
Police leadership styles and their attitudes have been regarded to be tightly bunched together yet this notion remains a grave controversy with the several theories contradicting with each other. Despite of the existence of numerous researchers investigating both constructs, only little study found that generates the correlation of leadership styles of police officers and their attitudes but also weakened by certain scholars who negated this belief. Hence, this was styles and attitudes of police officers as well as the level of their leadership styles in terms of transformational and transactional leadership. Through the employment of mean and Pearson product moment correlation, the data collected from the 80 non- commissioned police officers selected randomly by the researches were analyzed and interpreted. The employment of descriptive- correlational research design enables this study to descriptively interpret the results computed from the responses of the police officers-participants. Generated findings summarized that leadership and police attitude level are very high and have been embodied among the police officers. Thus, there is a significant relationship between leadership styles of police officers and their attitudes.
Keywords: Criminology -- Criminology -- Undergraduate thesis